Affecting Microstructure and Properties of Additively Manufactured AISI 316L Steel by Rotary Swaging - Kunčická, Lenka; Kocich, Radim; Benč, Marek; Dvořák, Jiří (Materials (Basel, Switzerland), 2022)
The presented work focused on the development of the microstructural and mechanical properties of a AISI 316L stainless steel workpiece prepared through additive manufacturing and subsequently processed by hot rotary swaging. In order to characterize the effects of swaging on the structural development, samples were taken for electron microscopy scanning and microhardness measurements were taken after each swaging reduction. The as-built and final swaged pieces were also subjected to tensile testing at room temperature and at 900 °C. The structural analyses showed that the hot swaging introduced a substructural formation; low angle grain boundaries prevailed over high angle ones after each pass. The swaging also imparted an almost complete elimination of the porosity and significant grain size; the average grain area decreased from the original value of 365.5 µm2 to 4.4 µm2 after the final swaging pass. The changes in the texture between the passes were negligible, however, the grain refinement went hand in hand with the microhardness increase (up to almost 300 HV1). The results of the tensile testing confirmed that the mechanical properties of the swaged pieces which improved dramatically and remained favorable up to high temperatures.
Keywords: selective laser melting; 316L stainless steel; rotary swaging; microstructure; mechanical properties